Inovasi Layanan Khusus Akhir Pekan (LAKSA) dalam Meningkatkan Kualitas Pelayanan Publik di Kantor Imigrasi Kelas I Non TPI Tangerang - Syahira, Devina; Handayani, Riny; Rizkiyani, Tiwi (Policy, Law and Political Research Center, 2024)
This study examines the implementation of Weekend Special Service (LAKSA) innovation at the Tangerang Class I Non-TPI Immigration Office, which still faces challenges in scheduling and accessibility of Immigration Introduction Letters—using a descriptive qualitative method through observation, interviews, and literature study with purposive informant selection technique and data analysis using Miles, Huberman, and Saldana (2014) model. The results show that LAKSA implementation still needs to be optimal. The relative advantage aspect shows an acceleration in passport services. The compatibility aspect runs well according to applicants' needs and regulations. However, the complexity aspect is still constrained by service accessibility in South Tangerang and Tangerang Regency areas. The liability aspect could be more optimal as no official trials involving the community have been conducted. The observability aspect is evident through social media socialization. It is recommended that the Immigration Office conduct a unique LAKSA satisfaction survey and expand its implementation.